Mechanical Behavior of Various Orthodontic Retraction Springs - Setiawan, Rachman; Idris, Muhammad; Prakasa, Tito Dwi (ITB Journal Publisher, LPPM ITB, 2011)
Retraction spring is a type of orthodontic apparatus that is used to move a tooth with respect to another by utilizing its spring back effect. It is made of metallic wire formed to individual orthodontic cases. A specific geometry results in a set of force system, consisting of forces and moments, that provides specific movement effect when it is pre-activated to the adjacent teeth. Currently, orthodontists select its geometry depending on their knowledge and experience. It is based on separate and less-than-comprehensive literatures that not all orthodontists have access to. It may result in inaccuracies in treating individual tooth retraction case. Engineering approach to estimating retraction spring structural behavior is proposed through analytical, numerical and empirical methods. Castigliano method is used as the analytical approach, whilst finite element method is used as the numerical approach. The two simulation approaches were compared to the experiments to obtain the best simulation model. The behavior of the simulation models agree well with those of experiments. Hence, the simulation models were used to simulate a large number of geometries to form database of structural behavior of retraction spring that could be used in the geometry selection by orthodontists.